Ecological Test of New Varieties of Fine Fiber Cotton (Texas Journal of Multidisciplinary Studies, 2023)
The article presents the results of ecological testing of new varieties of thin fiber cotton at the Scientific Research Institute of Fine Fiber Cotton .